Fine‐tuning of dual‐SMAD inhibition to differentiate human pluripotent stem cells into neural crest stem cells. (29th July 2021) - Kim, Hyun‐Mun; Noh, Hye Bin; Lee, Sang‐Hyuk; Lee, Kun‐Gu; Chang, Bomi; Cheong, Eunji; Lee, C. Justin; Hwang, Dong‐Youn
Abstract: Objectives: The derivation of neural crest stem cells (NCSCs) from human pluripotent stem cells (hPSCs) has been commonly induced by WNT activation in combination with dual‐SMAD inhibition. In this study, by fine‐tuning BMP signalling in the conventional dual‐SMAD inhibition, we sought to generate large numbers of NCSCs without WNT activation. Materials and methods: In the absence of WNT activation, we modulated the level of BMP signalling in the dual‐SMAD inhibition system to identify conditions that efficiently drove the differentiation of hPSCs into NCSCs. We isolated two NCSC populations separately and characterized them in terms of global gene expression profiles and differentiation ability. Results: Our modified dual‐SMAD inhibition containing a lower dose of BMP inhibitor than that of the conventional dual‐SMAD inhibition drove hPSCs into mainly NCSCs, which consisted of HNK + p75high and HNK + p75low cell populations. We showed that the p75high population formed spherical cell clumps, while the p75low cell population generated a 2D monolayer. We detected substantial differences in gene expression profiles between the two cell groups and showed that both p75high and p75low cells differentiated into mesenchymal stem cells (MSCs), while only p75high cells had the ability to become peripheral neurons. Conclusions: This study will provide a framework for the generation and isolation of NCSC populations for effective cell therapy for peripheral neuropathies and MSC‐based cell therapy. Abstract : The derivation of NCSCs from hPSCs by a modified dual‐SMAD inhibition without WNT activation. We showed that the p75high population formed spherical cell clumps, while the p75low cell population generated a 2D monolayer. When the two groups were isolated and differentiated, both p75high and p75low cells were differentiated into MSCs, but peripheral neurons differentiated only from p75high cells.